A retrospective study of individualized endovascular treatment for symptomatic intracranial atherosclerotic stenosis in patients with ischemic stroke/transient ischemic attack - Mao, Lun-Lin; Ma, Ai-Jin; Liu, Zhi-Qing; Zhang, Jin; Xu, Yuan-Feng; Chen, Wen-Ya; Cao, Yong-Jun (Frontiers in Neurology, 2022)
Background Endovascular treatment (EVT) is one of the effective treatment procedure for the symptomatic intracranial atherosclerotic stenosis (sICAS). Aim and methods We evaluated the efficacy and safety of individualized endovascular treatment for sICAS patients. Clinical and imaging follow-ups were carried out to collect the data of 29 sICAS patients after 6 months of individualized endovascular treatment. Different treatment strategies are selected based on arterial access and lesion morphology of patients. If standard surgical path, narrow artery straight, stenosis length ≤10 mm, then the appropriate specifications of balloon-mounted stent (BMS) treatment. the surgical path is tortuous, the narrow artery is curved, the angle is apparent, the diameter of the near and far ends is significantly different, or the length of the stenosis is >10 mm, self-expanding stent (SES) with appropriate specifications is selected for treatment. If the narrowed artery is hyper flexed and the surgeon deems stenting inappropriate, balloon dilation angioplasty (BDA) treatment is chosen. Results and conclusion 31 lesions of 29 sICAS patients received endovascular treatment. The median age was 61 years (IQR 54–69 years). The median preoperative stenosis was 90% (IQR 80–95%), and the mean stenosis length was (8.10 ± 3.27) mm. The most commonly used surgical procedure was Balloon-Mounted Stent (BMS) in 19 cases (65.52%), Self-expanding Stent (SES) in seven cases (24.14%), Balloon Dilation Angioplasty (BDA) in three cases (10.34%). (11.86 + 1.46 mm) was greater than that in the BMS group (6.14 + 1.59 mm) (P < 0.001). The median stenosis was 90% (IQR 80–92.5%) in the BMS group, lower than 99% (IQR 95–100%) in the SES group (P < 0.001). The median post-operative residual stenosis was 20% (IQR 15–25%), significantly improved compared with preoperative (P < 0.001). The success rate of the surgical technique was 93.10% (27/29). One patient (3.45%) had IS recurrence within 48 h after surgery, and the restenosis rate within 6 months after surgery was 6.90% (2/29). No patient died or had recurrent IS. Our data demonstrated that individualized endovascular treatment method could be potentially significant and safe for sICAS patients. This study will provide an important reference for the endovascular treatment of sICAD.